2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20190233
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology life quality index in patients with persisting and recurrent dermatophytoses

Abstract: <p class="abstract"><strong>Background:</strong> Dermatophytosis is the most common fungal infection, which has recurrent and persisting course because of topical steroid abuse, irregular treatment and poor hygiene. Dermatology life quality index (DLQI) is a questionnaire based survey method to assess the impact and severity of many dermatology specific diseases and infections. There is paucity in the literature on the impact of dermatophytosis on the quality of life (Qol). The aim of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 12 publications
4
9
1
Order By: Relevance
“…In the present study, it was found that the DLQI score had a positive correlation with duration, that is QOL is more impaired in TC patients if the duration of the disease is more. Similar findings were reported in the study conducted by Rajashekar TS et al [18]. The minimum body surface area involved was < 2% and the maximum was >10% in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, it was found that the DLQI score had a positive correlation with duration, that is QOL is more impaired in TC patients if the duration of the disease is more. Similar findings were reported in the study conducted by Rajashekar TS et al [18]. The minimum body surface area involved was < 2% and the maximum was >10% in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is no statistically significant correlation between Gender & DLQI score (P=0.2828) in the present study. The study by Rajashekar TS et al, had also mentioned that DLQI scores compared between males and females does not show any statistical significance [18]. The least duration of disease in the present study was less than 10 weeks & the highest duration was more than 60 weeks.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations